Distribution and enrichment of trace metals in surface marine sediments in the Gulf of Pozzuoli and off the coast of the brownfield metallurgical site of Ilva of Bagnoli (Campania, Italy). Issue 1 (15th November 2017) - Trifuoggi, Marco; Donadio, Carlo; Mangoni, Olga; Ferrara, Luciano; Bolinesi, Francesco; Nastro, Rosa Anna; Stanislao, Corrado; Toscanesi, Maria; Di Natale, Gabriella; Arienzo, Michele
Abstract: The distribution of metals in surface sediments of Gulf of Pozzuoli (GoP), embedding the former second Italian largest integrated steelworks of Bagnoli, was studied based on sediment dispersal, quality guidelines (SQGs) and quantitative pollution indices of the respective metals. As, Cd, Hg, Pb, Zn largely exceeded the limits. Hg had a mean of 5.8 mg/kg, twentyfold higher the rule, accumulating primarily near Bagnoli site. The mean effective range quotient, m-ERM-Q, revealed a high potential for negative biological effects especially in the area nearby the Bagnoli site. The enrichment factor (EF) values were outstandingly high, > 1.5 with values which were often ≥ 100. The geoaccumulation index, Igeo, was very critical for Cr, Cu, Hg and Ni, showing an Igeo in the range of strongly polluted (4 < Igeo < 5) and very strongly polluted (Igeo > 5). The principal component analysis (PCA) and Pearson's correlation matrix (CM), excluded significant contribution from weathering products. Highlights: Distribution of heavy metals in surface sediments in the Gulf of Pozzuoli Ecological risk assessment of sediment toxicity Metal enrichment factor and geo-accumulation index for determination of pollution Multivariate analysis and sources attribution